2016
DOI: 10.1021/acsenergylett.6b00511
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 1% Lanthanum Dopant on Carbonaceous Fuel Redox Reactions with an Iron-Based Oxygen Carrier in Chemical Looping Processes

Abstract: The cyclic redox reactivity of metal oxides plays an important role in many energy fields such as fuel cells, photocatalysis, and chemical looping. In chemical looping systems, oxygen carriers are required to have high reactivity, recyclability, and high oxygen carrying capacity. We utilize catalytic lanthanum dopants to dramatically change the reactivity with carbonaceous fuels while maintaining or even improving the recyclability of iron-based oxygen carriers. A low concentration of La dopant is applied to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…The calculated α-Fe 2 O 3 bulk lattice parameters were a = b = 5.04 Å and c = 13.83 Å, in good agreement with the experimental values ( a = b = 5.038 Å and c = 13.772 Å). The α-Fe 2 O 3 (001) surface with Fe-O 3 -Fe- termination was chosen to model the iron oxide slab with a thickness of ~15 Å 29 . Fe 2 O 3 nanoparticles were modeled by a three-dimensional periodic arrangement with a large cubic cell of 5 × 5 × 5 nm 3 to minimize lateral interactions.…”
Section: Methodsmentioning
confidence: 99%
“…The calculated α-Fe 2 O 3 bulk lattice parameters were a = b = 5.04 Å and c = 13.83 Å, in good agreement with the experimental values ( a = b = 5.038 Å and c = 13.772 Å). The α-Fe 2 O 3 (001) surface with Fe-O 3 -Fe- termination was chosen to model the iron oxide slab with a thickness of ~15 Å 29 . Fe 2 O 3 nanoparticles were modeled by a three-dimensional periodic arrangement with a large cubic cell of 5 × 5 × 5 nm 3 to minimize lateral interactions.…”
Section: Methodsmentioning
confidence: 99%
“…DFT calculations indicated that 1 % La dopant preferred to migrate to the outermost layer of the iron oxide surface with the least surface energy of 1.39 J/m 2 (Figure 14(c)), on which CH 4 adsorbed (0.12 eV vs . 0.06 eV) and dissociated more facilely compared with Fe sites in un‐doped Fe 2 O 3 (Figure 14(b)) [63] . Such the promotional influence on CH 4 conversion was also reported in 1 % Cu doped Fe 2 O 3 wherein Cu dopants was not enriched on the surface like La and was able to favor the formation the oxygen vacancies in Fe 2 O 3 , which significantly lowers the barrier of CH 4 activation by the path of CH x species adsorbed on the neighboring oxygen vacancies and H on Cu adsorption sites [64] .…”
Section: Oxygen Carriersmentioning
confidence: 99%
“… (a) Conversion of La‐doped and undoped Fe 2 O 3 for 5 min reduction at 1000 °C with CH 4 ; (b) Energy profile of CH 4 activation on the Fe 2 O 3 surface and on the 1 % La‐doped Fe 2 O 3 surface; (c) Optimized structure of α‐Fe 2 O 3 (001) surfaces with 1 % La dopant in four different sites. Purple, red, and blue balls represent Fe, O, and La atoms, respectively [63] . Reproduced with permission from Ref.…”
Section: Oxygen Carriersmentioning
confidence: 99%
“…Since metal oxides play a crucial role in the CLPOM, substantial research efforts have been devoted to the design and development of efficient oxygen carriers, which have high oxygen-carrying capacities, high selectivities toward syngas, and excellent redox reactivities [8]. Metal oxides such as nickel oxides [9][10][11], copper oxides [12], ferrite oxides [8,[13][14][15], and tungsten oxides [16] have been applied in CLPOM and have shown great potential.…”
Section: Introductionmentioning
confidence: 99%